THE COMPARISON OF CLASSICAL TAFSIR AND CONTEMPORARY INTERPRETATION REGARDING THE VERSES OF ASTROPHYSICS AND COSMOLOGY IN THE QUR’AN - Ansharullah, Azra; Imamuddin, Basuni (International Review of Humanities Studies, 2025)
As time progressed, various kinds of discoveries in the field of science emerged one by one, especially in the field of Astronomy and its "little brother" Astrophysics. This opens up opportunities for everyone to research things that have been researched from a new perspective, such as researching the Koran from a science and technology perspective. There are 310 instances in the Qur'an where the word "heaven" is mentioned, and within them, there are various statements regarding the nature, phenomena, and other things related to the sky. With the progress of technology, there is undoubtedly a gap in the interpretation and understanding of these verses. These verses can be examined in light of the discoveries of astronomers. In this research, the researcher examines verses related to astrophysical and cosmological phenomena by comparing classical and contemporary interpretations. The researcher briefly compares classical exegesis with contemporary interpretations. The research method in this study is qualitative, involving document analysis using Arabic linguistic and rhetorical theories. The researcher concludes that there are many verses in the Qur'an that can be studied from a scientific and technological perspective. As technology advances, more and more things align with the Qur'an as the gap in interpretation is filled by scientific discoveries.